Elevated Plasma Chemokines for Eosinophils in Neuromyelitis Optica Spectrum Disorders during Remission - Tong, Yanping; Yang, Tao; Wang, Jingwen; Zhao, Tianyou; Wang, Lei; Kang, Yuezhi; Cheng, Cuicui; Fan, Yongping (Frontiers in Neurology, 2018)
Background: A prominent pathological feature of neuromyelitis optica spectrum disorders (NMOSD) is markedly greater eosinophilic infiltration than that seen in other demyelinating diseases, like multiple sclerosis (MS). Eosinophils express the chemokine receptor CCR3, which is activated by eotaxins (CCL11/eotaxin-1, CCL24/eotaxin-2, CCL26/eotaxin-3) and CCL13 (monocyte chemoattractant protein-4). Moreover, CCL13 is part of the chemokine set that activates CCR2. The present study aimed to evaluate plasma levels of eotaxins (CCL11, CCL24, CCL26) and MCPs (CCL13, CCL2, CCL8, CCL7) in patients with NMOSD during remission. Methods: Healthy controls (HC; n = 30) and patients with multiple sclerosis (MS) (n = 47) and NMOSD (n = 58) in remission were consecutively enrolled in this study between January 2016 and August 2017. Plasma CCL11, CCL24, CCL26, CCL2, CCL8, CCL7, CCL13, tumor necrosis factor (TNF)-α and interleukin (IL)-1β levels were detected using the human cytokine multiplex assay. Results: Plasma CCL13, CCL11 and CCL26 levels were all significantly higher in patients with NMOSD than in HC and patients with MS. No significant differences were found in the CCL13, CCL11 or CCL26 levels between patients with NMOSD receiving and not receiving immunosuppressive therapy. The plasma levels of TNF-α and IL-1β, which stimulate the above chemokines, were higher in patients with NMOSD than in HC. There was no difference in CCL24 levels among the three groups. In most cases, the CCL7 levels were below the threshold value of the human cytokine multiplex assay, which is in line with other studies. Adjusted multiple regression analyses showed a positive association of CCL13 levels with the numbers of relapses after controlling gender, age, body mass index (BMI) and disease duration in patients with NMOSD. Conclusions: The study indicates that in NMOSD, overproduction of cytokines such as IL-1β and TNF-α during remission stimulates eosinophilic chemoattractants such as CCL13, CCL11, and CCL26, which in turn bind to their receptor (CCR3); this could lead to eosinophil hypersensitivity. These findings suggest that elevated secretion of CCL13, CCL11, and CCL26 may be a critical step in eosinophil recruitment during NMOSD remission.